2016
DOI: 10.1017/s1355617716000424
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Correlates of Successful Treatment of PTSD in Female Veterans

Abstract: Our finding that learning/memory predicted treatment success is consistent with previous studies. We extended these studies by showing that the effect was restricted to learning/memory, which is contrary to the executive function theory of PTSD. In contrast, the fact that only inhibition/switching significantly improved with better treatment success is consistent with its potential importance in maintaining PTSD symptoms. Future research should determine whether inhibition/switching abilities are a risk for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 49 publications
(131 reference statements)
3
42
2
Order By: Relevance
“…Is there any evidence of a dissociation between verbal and visual WM, especially in relation to symptom severity? Closer examination of this issue – including at the level of individual differences – could be informative in studies of treatment response to different psychotherapies (e.g., Haaland et al, 2016). The largest meta-analysis to date yielded a medium effect size ( d =−0.50) for the combined construct of attention/working memory but did not differentiate between verbal and visual WM (Scott et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Is there any evidence of a dissociation between verbal and visual WM, especially in relation to symptom severity? Closer examination of this issue – including at the level of individual differences – could be informative in studies of treatment response to different psychotherapies (e.g., Haaland et al, 2016). The largest meta-analysis to date yielded a medium effect size ( d =−0.50) for the combined construct of attention/working memory but did not differentiate between verbal and visual WM (Scott et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a pre‐post trial design, Haaland et al reported that mTBI history had no association with response to PTSD treatment among women veterans ( n = 42 females; 45% with mTBI history) . A small RCT ( n = 21; 33% female) reported a reduction in TBI and subclinical PTSD symptoms with Emotional Freedom Technique therapy; however, there were no significant associations with gender …”
Section: Resultsmentioning
confidence: 99%
“…There was no proof of differences during psychotherapy between patients who were and who were not taking serotonergic antidepressants. The significant improvements and effect sizes in our study are in line with a previous study, which found small‐ to medium‐sized improvements on indices of verbal learning/memory and inhibition/switching after group trauma‐focused psychotherapy and skills training in female veterans with PTSD (Haaland et al ., ). The results of the current study partly agree with a small study which found improvements in some aspects of executive functioning and not in others after a variety of psychotherapeutic treatments for PTSD (Walter et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The degree of change in PTSD symptoms over treatment was correlated with the degree of change in neuropsychological performance in the expected direction, but none of these relationships reached statistical significance. Relationships between neuropsychological changes and symptom change over treatment have rarely been studied in previous reports; one study found that improvements in inhibition/switching were related to treatment outcome, but improvements in verbal learning/memory were not (Haaland et al ., ). Taken together, these studies show that neuropsychological changes are not consistently related to the degree of change in PTSD symptoms, and neurocognitive alterations in PTSD may probably best be defined as both state‐related and trait markers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation